Studying The Lifestyle Of Modern High School Students (Eurasian Journal of Research, Development and Innovation, 2025)
The article covers the issues of nurturing a healthy lifestyle of high school students. The individual's acceptance of social values and norms occurs through individual needs, motives, mechanisms of activity and behavior. The school and education system are responsible for the educational process, but healthy lifestyle norms are not always instilled, and the health and healthy lifestyle of the younger generation are currently the main tasks in the development of the state and society. In this work, a survey of high school students in comprehensive schools and schools with a mathematical focus was conducted. Data on the students' lifestyle were obtained and processed, and the main shortcomings were identified.